2013
DOI: 10.1590/s0104-11692013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress in everyday nursing: hidden traces of power and resistance

Abstract: Objective: To know the strategies of resistance adopted by nursing staff, facing situations of moral distress, from an ethical perspective. Method: The authors conducted qualitative research through semi-structured interviews, with fifteen nursing staff members of a university hospital in the extreme south of Brazil, using textual discourse analysis and the theoretical reference of Foucault. Results: Two categories were constructed: denial of oneself and the other -in which one perceives that the nursing staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
38

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 7 publications
1
63
0
38
Order By: Relevance
“…11,31 Therefore, the work environment has been considered the factor that most influences the efficacy of nursing actions related to patient advocacy. 4,6,29,32 The efficacy of patient advocacy efforts does not depend only on the nurses' traits, skills, and the knowledge they hold as advocates, but also on a receptive environment.29 Therefore, it is important to note that advocacy always occurs in a social environment so that the identification of the characteristics of such an environment that can facilitate patient advocacy is essential.…”
Section: Patient Advocacy Barriers and Facilitatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,31 Therefore, the work environment has been considered the factor that most influences the efficacy of nursing actions related to patient advocacy. 4,6,29,32 The efficacy of patient advocacy efforts does not depend only on the nurses' traits, skills, and the knowledge they hold as advocates, but also on a receptive environment.29 Therefore, it is important to note that advocacy always occurs in a social environment so that the identification of the characteristics of such an environment that can facilitate patient advocacy is essential.…”
Section: Patient Advocacy Barriers and Facilitatorsmentioning
confidence: 99%
“…Many barriers, however, are faced by nurses, impeding them from satisfactorily fulfilling this role in accordance with their ideals. [10][11] Both Brazilian and international studies have identified that the practice of patient advocacy in the face of ethical conflicts can either generate relief or intensify moral distress if nursing workers are prevented from performing the role that corresponds to their ideals. 5,[11][12][13][14] Therefore, nurses experience moral distress when they recognize a need to advocate in favor of their patients but, due to external pressure, are prevented from proceeding with such an action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, o conhecimento localizado, situado e fugaz pode responder, de acordo com os interesses em jogo, pela diversidade de verdades existentes, ligadas ao contexto, ao tempo, ao lugar e à linguagem. 23 Nessa compreensão, configura-se um espaço em branco entre o conhecimento formado pelos trabalhadores do SAMU, que participaram na construção dos saberes, de funcionamento e organização desse serviço peculiar, e aquele colocado como saber técnico--científico e legal para o serviço. Os saberes desses profissionais estão entre as várias questões relegadas pelo saber chancelado institucionalmente, como os instituídos pelo Ministério da Saú-de e/ou pelas Secretarias Estadual e Municipal de Saúde para o funcionamento e organização dos serviços.…”
Section: Discussionunclassified
“…22 Entretanto, há de se considerar, nesse caso, que o atendimento irá ocorrer por força da normalização. Isso não implica dizer que não haja resistência, pois esta pode se manifestar a partir de outras expressões, 23 tais como demora na recepção do paciente, retenção de materiais como macas e colares cervicais, entre outras táticas dos serviços que recebem o usuário.…”
Section: Você Vai Pegar E Vai Levar (E14)unclassified